Modeling Low Income Vehicle Ownership in Cibadak District - Hendri Mulyana; Utamy Sukmayu Saputri; Ardin Rozadi; Lugovaya Nika Vyaceslavovna (Nusa Putra University, 2022)
The number and growth of vehicles is a separate problem related to the problem of sustainable transportation. In 2019, the number of motorized vehicles in Indonesia was recorded at more than 448 vehicles per 1,000 people. And specifically for motorcycles, it reaches 365 vehicles per 1,000 people. The growth of motor vehicles is significantly influenced by economic growth as measured by Gross Regional Domestic Product. When compared with the growth of motorized vehicles, it can be concluded temporarily that the high growth rate of motorized vehicles at the end of this decade has an impact on traffic problems on the highway. To see the trend between economic growth represented by regional gross domestic product and motorcycle growth, a model is needed to be useful for policymakers who handle the road in making decisions. The results showed that the growth model of motorcycles in Sukabumi can be approached with a linear regression equation. With the sample from the Cibadak sub-district, the area is classified as a low-income area.